Tobacco Industry and Sustainability: A Case of Indonesia Cigaretes Company - Marveys Wilfred Ayomi (APMBA (Asia Pacific Management and Business Application), 2013)
The following report is conducted to analyse global tobacco industry and evaluate the initiatives taken by the industry to promote sustainable business development. The purpose of the overall assessment of tobacco industry and sustainability is to determine the level of commitment that the industry gives to undertake issues addressed in sustainability. The elements discussed in this report outlined several key issues including the general outlook of the current industry operation as well as in the long run, damages caused by the industry activity affecting social, health and environmental conditions and Industry’s actions prior to sustainability. The discussion of tobacco industry actions in particular further examines sustainable initiatives implemented in economic, social, health and environment sectors. Close evaluation is carried out prior to each sector analyzing the commitmentof the industry to justify how devoted it is to bring about sustainable business practices. The second part of the discussion draws a practical analysis by comparing the nine principles of Epstein’ssustainability performance and the success of HM Sampoerna Tbk PT (One of Indonesia’s largest tobacco companies) sustainability performance. This report however bears a set of limitations and drawbacks such as a lack of deeper evaluation on the industry's initiatives in all sectors but particularly the environment aspect as well as its in sufficiency of data collection